Migrating transactions - Klein, J.; Reuter, A. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
Presents a concept that permits long activities to be broken into several steps using short transactions. The scheme maintains the consistency of the data and the correct termination of the transaction-set is guaranteed. Invariant data or program structures can be passed to subsequent decision points, permitting an application designer to specify those assumptions needed to produce the actions that make up the activity. The control of the activity is not fixed on a certain node making the execution of the activity independent of nodes.< >